Super-ionic conductor electrolyte, preparation method thereof, hybrid super-ionic conductor electrolyte, quasi-solid flexible super-ionic conductor electrolyte, alkaline battery super-ionic conductor electrolyte and energy storage equipment

By designing an ionic liquid [A]X composed of choline or its halide and pyrimidine carboxylic acid derivatives, the existing electrolytes have solved the problem of reduced conductivity and safety in the wide temperature domain, and the ultra-ion conductor electrolyte with ultra-high ionic conductivity and wide temperature domain characteristics have been achieved.

CN119890453AActive Publication Date: 2025-04-25YIMEILAI (GUANGZHOU) MEDICAL TECH CO LTD

Patent Information

Application Number
CN202510062366.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The conductivity of existing ionic electrolytes decreases at low temperatures, which easily lead to thermal decomposition and safety problems at high temperatures, and cannot meet the requirements of a wide operating temperature range.

Method used

A superion conductor electrolyte is designed, using choline or its halide as the cationic part and a pyrimidine carboxylic acid derivative as the anionic part. The ionic liquid [A]X formed has ultra-high ionic conductivity and wide temperature domain characteristics.

Benefits of technology

It achieves high ionic conductivity within the temperature range of -46℃~+270℃, improves the stability and safety of the electrolyte, and meets the ideal low-temperature electrolyte standards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890453A_ABST
    Figure CN119890453A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ionic liquid and new energy battery electrolyte compounding, in particular to a super-ionic conductor electrolyte and a preparation method thereof, a hybrid super-ionic conductor electrolyte, a quasi-solid flexible super-ionic conductor electrolyte, an alkaline battery super-ionic conductor electrolyte and energy storage equipment. The superaionic conductor electrolyte includes an ionic liquid [A] X, where [A] is derived from choline or a halide thereof, and X is derived from a pyrimidine carboxylic acid derivative. The super-ionic conductor electrolyte has ultrahigh ionic conductivity, thermal stability, electrochemical stability, non-volatility and non-flammability; the electrolyte has the duality of an ultra-high ionic conductor and a green solvent, and can completely replace a volatile organic solvent as a green solvent, so that the safety, stability and green environmental protection property of the battery electrolyte are improved. The wide-temperature-range ionic liquid electrolyte has the characteristics of wide-temperature-range ionic liquid electrolyte, accords with and exceeds the ideal low-temperature electrolyte standard, and is suitable for being applied to battery electrolyte, supercapacitor electrolyte and electrochemical sensors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials of ionic liquids and new energy battery electrolytes, and in particular to superionic conductor electrolytes and preparation methods thereof, hybrid superionic conductor electrolytes, quasi-solid-state flexible superionic conductor electrolytes, alkaline battery superionic conductor electrolytes and energy storage devices. Background Art

[0002] Electrolyte is one of the important components of electrochemical energy storage devices. The stability and ionic conductivity of electrolyte are the key to determining battery performance (Chen Renjie, Zhao Taolin, "Ionic Liquid Electrolytes", Science Press, first edition in 2023). The high conductivity of electrolyte is to reduce Li + Migration resistance is an important guarantee for improving battery rate performance, which determines the rapid charge and discharge performance of ion batteries. Improving the conductivity of electrolytes, especially the ion conductivity under low temperature conditions, is of particular significance for broadening the practical application range of lithium-ion batteries and realizing their application under extreme conditions (Li Fujun, ed., "Secondary Battery Science and Technology", Science Press, 2021, first edition).

[0003] Battery safety is considered to be a more important issue than performance, and the extensive use of volatile organic solvents poses a major threat to battery safety. Organic solvents are flammable and can easily cause temperature increases under conditions such as battery heating, overcharging or overdischarging, short circuits, and high temperatures, accelerating heat generation inside the battery. Excess heat accumulates inside the battery, causing thermal decomposition of the electrode active material or oxidation of the electrolyte, producing a large amount of gas, causing a sharp increase in the internal pressure of the battery, and triggering safety hazards such as combustion or explosion. Existing ionic electrolytes are ionic conductors in which lithium / sodium salts are dissolved in organic solvents. At present, the representative solvents with high dielectric constants are carbonate solvents such as ethylene carbonate (EC), which are almost indispensable components in all lithium-ion battery electrolytes (Chen Renjie, "Advanced Battery Functional Electrolyte Materials", Science Press, first edition in 2020).

[0004] Ionic liquids are organic salts composed entirely of positively charged cations and negatively charged anions, and have excellent electrochemical properties, such as wide electrochemical window, high ionic conductivity, and interfacial compatibility with electrode materials. Ionic liquids are also a kind of green design solvent, with good thermal stability, non-volatility and non-flammability. They can replace volatile organic solvents, reduce the adverse effects of electrolyte organic solvents on ionic conductivity, and further improve battery safety, reduce environmental and health damage, and realize truly green and clean battery resources. In short, the flexibility of ionic liquid design and ionic properties play an important role in electrochemical fields such as electrolytes, electrocatalysis, supercapacitors and electrochemical sensors (Xie Ze'an, Zhao Fangqian, Wang Yiyi, et al. Application of ionic liquids in electrochemistry [J]. Journal of Shenyang Normal University (Natural Science Edition), 2024, 42(01): 19-23.).

[0005] However, the performance of ionic liquids as electrolytes for energy storage devices still needs to be further optimized. The low conductivity and high viscosity of ionic liquids (their viscosity is 1 to 2 orders of magnitude higher than that of general organic solvents) will make the battery's rate performance unsatisfactory; in sodium-ion batteries, there is currently no ideal ionic liquid electrolyte formula that can simultaneously have a suitable potential window, fast ion conduction, and the ability to cope with extreme temperatures (Chen Renjie, Zhao Taolin, "Ionic Liquid Electrolytes", Science Press, first edition 2023).

[0006] Wide temperature range refers to a wide operating temperature range. With the continuous expansion of lithium battery application scenarios, the development of high and low temperature lithium battery technology is imminent, and liquid electrolytes with a wide operating temperature range are the key (Qi Shihan, Wang Zhongsheng, Guo Kanglong, et al. Research progress of wide temperature range lithium battery electrolytes [J]. Science Bulletin, 2022, 67(24): 2937-2949.). The standards for ideal low-temperature electrolytes are: (1) ionic conductivity higher than 1mS / cm at -40°C, (2) able to operate in a temperature range of -40°C to 60°C (Chen Renjie, Advanced Battery Functional Electrolyte Materials, Science Press, first edition, 2020). Existing electrolyte materials solidify at low temperatures, causing a significant decrease in ionic conductivity, and are prone to thermal decomposition at high temperatures, leading to safety issues, and cannot meet the requirements for a wide operating temperature.

[0007] Chinese patent CN 118530183 A discloses a pyrimidine ionic liquid, a preparation method thereof and its application. The pyrimidine ionic liquid has the advantages of low viscosity, stability to air and water, good compatibility with solutes, and excellent solubility, and is used as a functionalized ionic liquid solvent suitable for the biomedical field.

[0008] Chinese patent CN 106058312 B discloses a solid-state ionic liquid electrolyte, its preparation method and application. It is an imidazole ionic liquid hybrid solid-state ionic liquid electrolyte synthesized under almost anhydrous conditions and under the protection of nitrogen and argon. Its ionic conductivity at 0°C, 30°C and 60°C is 0.79, 1.91 and 4.79 mS / cm, respectively. The ionic conductivity is low and the operating temperature range is narrow, which cannot meet the ideal low-temperature electrolyte standards and higher electrochemical performance requirements.

[0009] Therefore, the purpose of the present invention is to design an ionic liquid electrolyte that can completely replace volatile organic solvents and further improve the ionic conductivity and operating temperature range of the electrolyte material.

[0010] In view of this, the present invention is proposed. Summary of the invention

[0011] The purpose of the present invention is to provide a superionic conductor electrolyte that can completely replace volatile organic solvents, and further improve the ionic conductivity and operating temperature range of the electrolyte material. The superionic conductor electrolyte has ultra-high ionic conductivity, thermal stability, electrochemical stability, non-volatility and non-flammability; it has the duality of a superionic conductor and a green solvent, can replace volatile organic solvents, and further improve the stability, safety and green environmental protection of battery electrolyte materials. It meets the ideal low-temperature electrolyte standard and can operate in the temperature range of -46°C to +270°C.

[0012] The present invention is achieved in that:

[0013] In a first aspect, the present invention provides a superionic conductor electrolyte, comprising an ionic liquid [A]X, wherein [A] represents a cation part, X represents an anion part, [A] is derived from choline or a halide thereof, and X is derived from a pyrimidinecarboxylic acid derivative.

[0014] In an optional embodiment, [A] is derived from any one of the compounds represented by the following structural formulas:

[0015]

[0016] In an optional embodiment, X is derived from a compound represented by the following structural formula:

[0017] Wherein, R1 is selected from H or hydroxyl, and R2 is selected from C1-C4 alkyl;

[0018] Preferably, X is derived from any one of the compounds represented by the following structural formulas:

[0019]

[0020] In an optional embodiment, the molar ratio of [A] to X is (1:1) to (14:1), preferably (2:1) to (10:1).

[0021] In an optional embodiment, the superionic conductor electrolyte is a pure aqueous superionic conductor electrolyte; the pure aqueous superionic conductor electrolyte does not contain any organic solvent;

[0022] Preferably, the superionic conductor electrolyte consists of water and ionic liquid [A]X;

[0023] Preferably, the concentration of the ionic liquid [A]X in the superionic conductor electrolyte is 10-70 wt%.

[0024] In a second aspect, the present invention provides a method for preparing the superionic conductor electrolyte described in the aforementioned embodiment, comprising: mixing and dissolving a raw material for forming a cation [A] and a raw material for forming an anion X;

[0025] Preferably, the preparation is carried out under non-vacuum conditions;

[0026] Preferably, the temperature of mixed dissolution is 30-50°C and the time is 10-30min;

[0027] Preferably, water is used to dissolve the raw materials for forming the cation [A] and the raw materials for forming the anion X;

[0028] Preferably, the process comprises: adding a raw material for forming a cation [A] and a raw material for forming an anion X into a small amount of water, stirring them conventionally at room temperature and pressure until they are completely dissolved, and synthesizing a required amount of ionic liquid [A]X in situ; and adding water until the total liquid volume is 100%.

[0029] In a third aspect, the present invention provides a hybrid superionic conductor electrolyte, which comprises the superionic conductor electrolyte described in the aforementioned embodiment and an electrolyte additive; the electrolyte additive is an electrolyte salt;

[0030] Preferably, the electrolyte salt is selected from any one of lithium salt, sodium salt, aluminum salt, magnesium salt, zinc salt, copper salt and metal oxide;

[0031] Preferably, the concentration of the electrolyte salt in the hybrid superionic conductor electrolyte is 5-30 wt %.

[0032] In a fourth aspect, the present invention provides a quasi-solid-state flexible superionic conductor electrolyte, comprising the superionic conductor electrolyte and an electrolyte additive as described in the aforementioned embodiment; the electrolyte additive is an electrolyte salt and a polymer; or the electrolyte additive is a polymer;

[0033] Preferably, the electrolyte salt is selected from any one of lithium salt, sodium salt, aluminum salt, magnesium salt, zinc salt, copper salt and metal oxide;

[0034] Preferably, the polymer is selected from any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, polyvinylidene fluoride, polyacrylamide, agar, carrageenan, xanthan gum, sodium alginate and cellulose;

[0035] Preferably, the concentration of the electrolyte salt in the quasi-solid flexible superionic conductor electrolyte is 5-30wt%;

[0036] The concentration of the polymer in the quasi-solid flexible superionic conductor electrolyte is 5-20 wt %.

[0037] In a fifth aspect, the present invention provides an alkaline battery superionic conductor electrolyte, which comprises the superionic conductor electrolyte described in the above embodiment and an electrolyte additive; the electrolyte additive is selected from any one of sodium hydroxide and potassium hydroxide;

[0038] Preferably, the concentration of the electrolyte additive in the alkaline battery superionic conductor electrolyte is 5-15 wt %.

[0039] In a sixth aspect, the present invention provides an energy storage device and an electrochemical sensor, which include at least one of the superionic conductor electrolyte described in the aforementioned embodiment, the hybrid superionic conductor electrolyte described in the aforementioned embodiment, the quasi-solid-state flexible superionic conductor electrolyte described in the aforementioned embodiment, and the alkaline battery superionic conductor electrolyte described in the aforementioned embodiment.

[0040] Preferably, the energy storage device comprises a battery and a supercapacitor;

[0041] Preferably, the battery comprises any one of a wide temperature range lithium ion battery, a sodium ion battery, a magnesium ion battery, a zinc ion battery, a copper ion battery and a fuel cell.

[0042] The present invention has the following beneficial effects: The embodiment of the present invention provides a superionic conductor electrolyte with ultra-high ionic conductivity, thermal stability, electrochemical stability, non-volatility and non-flammability. In particular, it has the duality of a superionic conductor and a green solvent, and then it can be used as an electrolyte itself. It can also replace volatile organic solvents in existing electrolytes to further improve the safety, stability and green environmental protection of the electrolyte. At the same time, it meets and exceeds the ideal low-temperature electrolyte standard, and can operate in the range of -46°C to +270°C, and then can be used to prepare lithium-ion batteries, sodium-ion batteries, magnesium-ion batteries, zinc-ion fuel cells, copper-ion batteries, supercapacitors and other energy storage devices and electrochemical sensors with a wide temperature range. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 A correlation diagram between the composition molar ratio and ionic conductivity of the ionic liquid [A]X provided in an embodiment of the present invention;

[0045] Figure 2 A correlation diagram between the mass concentration of the ionic liquid [A]X provided in an embodiment of the present invention and the ionic conductivity;

[0046] Figure 3 A differential scanning calorimetry (DSC) curve of the superionic conductor electrolyte provided in Example 1 of the present invention;

[0047] Figure 4 This is a thermogravimetric analysis (TGA) curve of the superionic conductor electrolyte provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0049] The challenge of ionic liquid electrochemical applications is to design ionic liquids with wide electrochemical windows and high conductivity. The main obstacle to the application of ionic liquid electrolytes in the prior art is low conductivity, which decreases with decreasing temperature. Obviously, the conductivity of ionic liquids depends on the composition of the ionic liquids, and also determines the thermodynamic stability and electrochemical stability of the ionic liquids. Therefore, the key to preparing ionic liquid electrolytes that meet practical needs lies in the correct ion pair screening and design.

[0050] The embodiment of the present invention adopts a de novo design strategy for hydrated ionic liquids to obtain a series of ionic liquids [A]X. It was unexpectedly found that the ionic liquid [A]X has ultra-high ionic conductivity characteristics. In preliminary tests, its room temperature ionic conductivity can be as high as 100mS / cm or more, and the stable temperature range is between -46°C and +270°C. It meets and exceeds the ideal low-temperature electrolyte standard. Therefore, the superionic conductor electrolyte provided by the embodiment of the present invention has both superionic conductor properties and wide temperature range properties, and is suitable for wide temperature range lithium-ion batteries, as well as non-lithium ion battery electrolytes such as sodium ions, magnesium ions, zinc ions, and copper ions, supercapacitor electrolytes, and electrochemical sensors.

[0051] Specifically, in a first aspect, the present invention provides a superionic conductor electrolyte, which includes an ionic liquid [A]X, wherein [A] represents a cationic part, X represents an anionic part, [A] is derived from choline or its halide, and X is derived from a pyrimidinecarboxylic acid derivative.

[0052] Specifically, [A] is derived from any one of the compounds represented by the following structural formulas:

[0053]

[0054] That is, [A] is derived from any one of choline, choline chloride, choline bromide, choline iodide, choline fluoride, choline chlorofluoride and β-methylcholine chloride.

[0055] X is derived from the compound represented by the following structural formula:

[0056] Wherein, R1 is selected from H or hydroxyl, and R2 is selected from C1-C4 alkyl;

[0057] Preferably, X is derived from any one of the compounds represented by the following structural formulas:

[0058]

[0059] The superionic conductor electrolyte provided by the embodiment of the present invention has ultra-high ionic conductivity characteristics and wide temperature range characteristics, and its room temperature ionic conductivity is as high as 100mS / cm or more, and the operating temperature range is between -46°C and +270°C. Therefore, it can be used as an electrolyte for energy storage devices such as wide temperature range batteries and supercapacitors, providing reliable power supply for equipment in extreme environments.

[0060] The stability and ionic conductivity of the electrolyte material are the key factors in determining the battery performance. Since the cation part [A] of the ionic liquid [A]X of the embodiment of the present invention is choline and its halide, the strong electronegativity of the halogen atom helps the dissociation of metal ions and anions, thereby affecting the electrochemical properties of the ionic liquid electrolyte, showing low migration energy barriers and ultra-high ionic conductivity, and thus having superionic conductor characteristics.

[0061] On the other hand, since the anion part X of the ionic liquid [A]X constituting the embodiment of the present invention is a pyrimidinecarboxylic acid derivative, it has a significant water structuring effect, which can make more water molecules in a bound water state, thereby weakening the influence of the solvent effect of water, which helps to reduce the battery capacity attenuation and safety problems caused by salting out on the negative electrode surface when the power battery is charged at low temperature and high rate.

[0062] Furthermore, the relationship between the molar ratio and concentration of the ionic liquid [A]X and the ionic conductivity was tested in the examples. The results showed that: (1) the ionic conductivity increased with the increase of the ratio of [A]:X in the ionic liquid [A]X. When the molar ratio of [A]:X was 8:1, the ionic conductivity approached the peak value and then slowly increased (see Table 1, Figure 1 ); (2) The ionic conductivity increases with the concentration of ionic liquid [A]X. When the concentration reaches 30-40 wt%, the ionic conductivity approaches the peak value and then begins to decrease (see Table 2, Figure 2 ).

[0063] Further, the molar ratio of [A] to X is (1:1) to (14:1), for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1 and 14:1, and any value between (1:1) and (14:1), for example, preferably (2:1) to (10:1);

[0064] Furthermore, the superionic conductor electrolyte is a pure water-based superionic conductor electrolyte; the pure water-based superionic conductor electrolyte does not contain any organic solvent; it only includes water and ionic liquid [A]X, and the concentration of ionic liquid [A]X in the superionic conductor electrolyte is 10-70wt%, for example, any value between 10%, 20%, 30%, 40%, 50%, 60% and 70%, etc.

[0065] Aqueous liquid electrolyte is a green electrolyte that does not cause environmental pollution. Compared with conventional non-aqueous electrolytes, it has advantages in cost, safety, and battery power density. In contrast, existing lithium-ion batteries use anhydrous organic solvents containing lithium ions as electrolytes, and the organic solvents used are not only toxic but also flammable. In addition, the production cost is also significantly increased due to the anhydrous operating environment, which limits its application in large-scale energy storage and other fields. Therefore, replacing organic solvent electrolytes with aqueous electrolytes is considered to be one of the effective methods (Chen Renjie, "Advanced Battery Functional Electrolyte Materials", Science Press, first edition in 2020).

[0066] Furthermore, since the raw materials for forming the ionic liquid [A]X are all non-toxic, harmless and biodegradable from natural sources, they are completely green and biocompatible.

[0067] In a second aspect, the present invention provides a method for preparing the superionic conductor electrolyte described in the aforementioned embodiment, comprising: mixing and dissolving a raw material for forming a cation [A] and a raw material for forming an anion X.

[0068] Specifically, the raw materials for forming the cation [A] and the raw materials for forming the anion X are sequentially added into a small amount of water, mixed and dissolved at room temperature and pressure, firstly the required amount of ionic liquid [A]X is synthesized in situ, and then water is added to make the total liquid volume 100%; preferably, the temperature of mixed dissolution is 30-50°C, and the time is 10-30min.

[0069] In a third aspect, the present invention provides a hybrid superionic conductor electrolyte. Since the superionic conductor electrolyte provided by the embodiment of the present invention has the duality of a superionic conductor and a green solvent, it can completely replace the volatile organic solvent in the existing electrolyte, further improving the safety, stability and green environmental protection of the electrolyte material.

[0070] The metal cations doped in the electrolyte rotate with the surrounding anions through the interaction of orientation forces and induction forces, and always rotate in the direction of reducing the energy barrier of the metal ions, allowing metal ions such as lithium ions to migrate quickly along the path of minimum energy, further improving the ionic conductivity of the electrolyte.

[0071] Specifically, ionic liquid [A]X can replace organic solvents such as carbonate, nitrile, ether and other volatile electrolyte solvents commonly used in existing electrolyte technology, optimize carbonate-centered electrolyte formulations, avoid metal reactions and interface instability caused by excessive carbonate, strengthen the electrode electrolyte interface structure, and reduce interface impedance. It provides a better lithium ion conduction path than existing electrolytes and optimizes the compatibility of electrolytes and electrode materials.

[0072] Furthermore, different electrolyte salts, such as lithium salts, sodium salts, aluminum salts, magnesium salts, zinc salts, copper salts and metal oxides, can be added without organic solvents to construct hybrid superionic conductor electrolytes, and the battery electrolyte performance can be further optimized to make it suitable for applications under different conditions. For example, only a small amount of lithium trifluoromethanesulfonyl imide (LiTFSi, 5wt%) can be added to significantly improve the ionic conductivity of the superionic conductor electrolyte (~120mS / cm).

[0073] The concentration of the electrolyte salt in the hybrid superionic conductor electrolyte is 5-30 wt%, for example, 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt% and 30 wt%, etc., any value between 5-30 wt%.

[0074] Furthermore, since the superionic conductor electrolyte provided by the embodiment of the present invention can be easily and conveniently dissolved into different electrolyte salts without organic solvents, more strategically significant low-cost sodium ion, magnesium ion, zinc ion and other non-lithium ion battery hybrid electrolytes can be prepared. Unlike lithium ion batteries, sodium ion batteries are generally believed to have excellent fast charging characteristics and low-temperature performance, becoming the first choice for the next generation of non-resource-limited high-efficiency energy storage systems.

[0075] Furthermore, since there is no need to add a large amount of organic solvent, the hybrid superionic conductor electrolyte can be prepared by conventional stirring at room temperature and pressure, thereby further simplifying the electrolyte composition and preparation process, and preparing the hybrid superionic conductor electrolyte by a simple, low-cost, low-energy, and pollution-free process, further optimizing the production process, electrochemical properties, and extreme environmental applicability of the ionic liquid electrolyte.

[0076] In a fourth aspect, the present invention provides a quasi-solid-state flexible superionic conductor electrolyte, which further optimizes the performance and environmental applicability of battery electrolytes and improves battery performance. For example, it can be used for battery electrolytes in fields such as wearable devices, biomedical engineering, etc., which have higher requirements for safety and convenience, as well as supercapacitors and electrochemical sensors.

[0077] Since the superionic conductor electrolyte provided by the embodiment of the present invention has the dual properties of a superionic conductor and a green solvent, a quasi-solid-state flexible superionic conductor electrolyte can be simply and conveniently prepared without the need for an organic solvent by directly mixing the polymer with the electrolyte salt or simply dissolving the polymer directly in the superionic conductor electrolyte while maintaining its superionic conductor properties.

[0078] The polymer is selected from any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, polyvinylidene fluoride, polyacrylamide, agar, carrageenan, xanthan gum, sodium alginate and cellulose. The mass concentration of the polymer in the quasi-solid-state flexible superionic conductor electrolyte is 5-20%, for example, any value between 5%, 10%, 15%, 20%, etc.

[0079] The electrolyte salt is selected from any one of lithium salt, sodium salt, aluminum salt, magnesium salt, zinc salt, copper salt and metal oxide. The mass concentration of the electrolyte salt in the quasi-solid flexible superionic conductor electrolyte is 5-30%, for example, any value between 5%, 10%, 15%, 20%, 25% and 30%, etc.

[0080] In a fifth aspect, an embodiment of the present invention provides an alkaline battery superionic conductor electrolyte, which includes the superionic conductor electrolyte described in the above embodiment and an electrolyte additive; the electrolyte additive is selected from any one of sodium hydroxide and potassium hydroxide. For example, the concentration of the electrolyte additive in the alkaline battery superionic conductor electrolyte is 5-15wt%. For example, any value between 5-15wt%, such as 5wt%, 10wt%, and 15wt%.

[0081] In a sixth aspect, the present invention provides an energy storage device and an electrochemical sensor, which include at least one of the superionic conductor electrolyte described in the aforementioned embodiment, the hybrid superionic conductor electrolyte described in the aforementioned embodiment, the quasi-solid-state flexible superionic conductor electrolyte described in the aforementioned embodiment, and the alkaline battery superionic conductor electrolyte described in the aforementioned embodiment, wherein the energy storage device includes a battery and a supercapacitor; for example, the battery includes any one of a wide temperature range lithium-ion battery, a sodium-ion battery, a magnesium-ion battery, a zinc-ion battery, a copper-ion battery, and a fuel cell.

[0082] Furthermore, since the conductive layer is the core component of the electrochemical sensor for converting and transmitting signals, and the vapor pressure of the ionic liquid is almost negligible, the electrochemical sensor based on the superionic conductor electrolyte can work stably for a long time in an open environment or even under vacuum conditions without performance loss, and further improve the conductivity, responsiveness and stability of the electrochemical sensor.

[0083] In summary, the superionic conductor electrolyte provided by the embodiment of the present invention has the following characteristics:

[0084] (1) Duality of superionic conductor and green solvent: Due to the natural low viscosity characteristics of the ionic liquid [A]X (~95-285mPa·s), the superionic conductor electrolyte provided by the embodiment of the present invention has the duality of superionic conductor and green solvent. The polymer and electrolyte salt can be directly dissolved in the superionic conductor electrolyte without organic solvent, so that an aqueous, hybrid, quasi-solid flexible superionic conductor electrolyte can be simply and conveniently prepared without damaging its superionic conductor properties. Even when a high polymer content is formed and a nearly non-flowing quasi-solid gel is formed, its ionic conductivity is still as high as 13mS / cm.

[0085] In contrast, the conductivity of metal halide solid electrolytes is basically between 0.01 and 0.1 mS / cm, and rarely reaches 10 mS / cm (Wang Weizong, Zhao Hongshun, Zhao Qian, et al. Computational simulation-assisted research on chloride solid electrolytes for lithium-ion batteries [J]. Chinese Science: Chemistry, 2024, 54(07): 991-1011.).

[0086] (2) Characteristics of wide temperature range ionic liquids: Wide temperature range refers to a wide operating temperature range. In application scenarios such as electric vehicles and portable electronic devices, lithium batteries only need to meet an operating temperature of 15 to 35°C. However, in some special application scenarios, lithium batteries need to exceed this temperature range. For example, the petroleum industry requires lithium batteries to adapt to an operating environment of about 80°C, and lithium batteries used in robots working in extreme environments even need to operate stably in an environment of ~150°C; in terms of low temperatures, application scenarios such as polar exploration and aerospace industry require lithium batteries to operate in an environment of -40°C or even -80°C. Too low an operating temperature will slow down the kinetics of the electrochemical reaction in the lithium battery, making it difficult to work (Qi Shihan, Wang Zhongsheng, Guo Kanglong, et al. Research progress in wide temperature range lithium battery electrolytes [J]. Science Bulletin, 2022, 67(24): 2937-2949.).

[0087] The results of thermodynamic stability tests on the superionic conductor electrolyte provided by the embodiment of the present invention show that its glass transition temperature is as low as -46.2°C and its thermal decomposition temperature is +272.4°C. This indicates that the superionic conductor electrolyte provided by the embodiment of the present invention remains stable in the temperature range of -46°C to +270°C, has the characteristics of a wide temperature range ionic liquid electrolyte, meets and exceeds the ideal low-temperature electrolyte standard, and further expands the applicability of battery electrolytes under extreme environmental conditions.

[0088] (3) Non-volatility and non-flammability: Battery safety is considered to be a more important issue than performance. In fact, under existing technologies, traditional lithium-ion batteries all use organic solvents (EC+DMC, EC+DEC, EC+DMC+EMC, EC+DMC+DEC, etc.) as electrolytes, and their safety has become the biggest problem. In order to improve its safety performance, researchers have explored the use of polymer electrolytes, but the lower ion conductivity and higher ohmic drop of polymers hinder its application (National Natural Science Foundation, Chinese Academy of Sciences, "China's Discipline Development Strategy: Chemical Process Intensification", Science Press, first edition in 2018).

[0089] In contrast, ionic liquids are non-volatile and non-flammable, and therefore can greatly improve the safety of existing battery electrolytes without compromising battery electrolyte performance.

[0090] (4) Unique double-layer structure: Compared with lithium-ion batteries, capacitors can have higher energy density without sacrificing power density. Among them, double-layer capacitors can withstand tens of thousands of ultra-long cycle life due to their fast charging and discharging speeds and the absence of electrochemical reactions during the process. In principle, there are two ways to increase the energy density of double-layer capacitors: one is to maximize the double-layer capacitance per unit area, and the other is to maximize the interface area per unit volume. Obviously, method one is the key, and the unique double-layer structure of ionic liquids at the interface provides conditions for the application of double-layer capacitors (National Natural Science Foundation, Chinese Academy of Sciences, "China's Discipline Development Strategy: Chemical Process Intensification", Science Press, first edition 2018).

[0091] In terms of microstructure, the short-range ion-ion interactions in ionic liquids have an important influence on the properties of ionic liquids and their interfaces, giving them unique electrochemical properties, manifested as special charge transfer methods and double-layer structures. That is, the double layer of ionic liquids at the interface is a multiple ion layer formed by alternating anion and cation layers, rather than a diffuse double layer in a conventional aqueous solution. Therefore, the superionic conductor electrolyte provided in the embodiments of the present invention is used in supercapacitors to improve the energy density, operating temperature range, and safety performance of existing supercapacitors.

[0092] (5) Properties of proton ionic liquids: According to the acid-base proton theory, the compounds choline and its halides, and pyrimidine carboxylic acid derivatives that form ionic liquids [A]X can accept and donate protons, respectively, and have the properties of proton ionic liquids. The exchangeable and reactive active protons in its structure are rapidly transferred between electrodes, making it suitable for use as electrolytes in fuel cells. In addition, ionic liquids are also highly promising catalyst layer additives that can promote redox reactions in fuel cells (Chen Renjie, Zhao Taolin, "Ionic Liquid Electrolytes", Science Press, first edition 2023).

[0093] Therefore, compared with the prior art, the superionic conductor electrolyte provided by the embodiment of the present invention has the duality of superionic conductor and green solvent, wide temperature range and good safety. Therefore, it is suitable for wide temperature range lithium-ion batteries, as well as non-lithium-ion battery electrolytes such as sodium ions, magnesium ions, zinc ions, copper ions, alkaline battery electrolytes, fuel cell electrolytes, supercapacitors and electrochemical sensors. At the same time, the microscopic double-layer structure characteristics of ionic liquids can further improve the energy density, operating temperature range and safety of existing supercapacitors.

[0094] Materials: 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, 5-hydroxy-2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid (100%, Merck), choline, choline chloride (90%, McLean), choline bromide, choline iodide, β-methylcholine chloride, lithium bromide, lithium trifluoromethanesulfonyl imide, lithium hexafluorophosphate, sodium alginate (98-99%, AR, Aladdin), polyvinyl pyrrolidone K-90 (Ashland), polyvinyl alcohol 1799 (analytical grade, Zhonglian), PEG-1450NF (Dow), sodium chloride, sodium hydroxide, potassium hydroxide, magnesium sulfate (analytical grade, Xiyu), cerium oxide (Guangli).

[0095] Detection method:

[0096] Ionic conductivity (Λ) test: Direct measurement method using conductivity meter (DDS-307A), actual test temperature of room temperature ionic conductivity is 20-25 degrees Celsius, actual test temperature of low temperature ionic conductivity is stable at -19.1 degrees Celsius. Unit: mS / cm;

[0097] Thermal stability window (ΔT) test: glass transition temperature, using differential scanning calorimetry (DSC, NETZSCH DSC204F1) thermal analysis method; thermal decomposition temperature, using thermogravimetric analysis (TGA, NETZSCH STA 2500) thermal analysis method.

[0098] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0099] Example 1

[0100] Embodiment 1 of the present invention provides a method for preparing a superionic conductor electrolyte, comprising: adding choline chloride (CHC) and 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, raw materials for forming [A]X, to a small amount of water in sequence according to the composition molar ratio (mol) and mass concentration (wt%) in Table 1, stirring for 10 to 30 minutes at room temperature until completely dissolved; and then adding water to a total liquid volume of 100%, thereby obtaining the superionic conductor electrolyte of Embodiment 1.

[0101] The composition and physicochemical properties of Example 1 are summarized in Table 1.

[0102] The ionic conductivity (Λ, unit: mS / cm) and pH value of a group of superionic conductor electrolyte solutions with different composition molar ratios and the same concentration provided in Example 1 were tested at room temperature (~25°C) to obtain a correlation index between the [A]:X molar ratio in the ionic liquid [A]X and the ionic conductivity.

[0103] The results show that the ionic conductivity of the superionic conductor electrolyte provided in Example 1 increases with the increase in the molar ratio of [A]:X in the ionic liquid [A]X. When the molar ratio of [A]:X is 8:1, the ionic conductivity approaches the peak value and then rises slowly (see Table 1, Figure 1 ).

[0104] Table 1 Composition and physicochemical properties of Example 1

[0105]

[0106] The molar ratios are rounded to integers.

[0107] Example 2

[0108] Embodiment 2 of the present invention provides a method for preparing a superionic conductor electrolyte, comprising: adding choline chloride (CHC) and 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, raw materials for forming [A]X, to a small amount of water in sequence according to the composition molar ratio (mol) and mass concentration (wt%) in Table 2, stirring for 10 to 30 minutes at room temperature until completely dissolved; then adding water to a total liquid volume of 100%, thereby obtaining the superionic conductor electrolyte of Embodiment 2.

[0109] The composition and physicochemical properties of Example 2 are summarized in Table 2.

[0110] The ionic conductivity (Λ, unit: mS / cm) and pH value of a set of superionic conductor electrolyte solutions with the same composition molar ratio and different concentrations provided in Example 2 were tested at room temperature (~25°C) to obtain a correlation index between the mass concentration of the ionic liquid [A]X and the ionic conductivity.

[0111] The results show that the ionic conductivity of the superionic conductor electrolyte provided in Example 2 increases with the increase in the mass concentration of the ionic liquid [A]X. When the concentration of [A]X reaches 30-40 wt%, the ionic conductivity approaches the peak value and then begins to decrease (see Table 2, Figure 2 ).

[0112] Table 2 Composition and physicochemical properties of Example 2

[0113]

[0114] The molar ratios are rounded to integers.

[0115] Embodiment 3-8

[0116] Embodiments 3 to 8 of the present invention provide a method for preparing a superionic conductor electrolyte, comprising: adding the raw materials choline chloride (CHC), choline bromide (CHB), choline iodide (CHI), β-methylcholine chloride (CHM), choline (CHO), and pyrimidinecarboxylic acid derivatives for forming [A]X to a small amount of water in sequence according to the composition molar ratio (mol) and mass concentration (wt%) in Table 3, stirring for 10 to 30 minutes at room temperature until completely dissolved, first synthesizing the required amount of ionic liquid [A]X in situ; then adding water to a total liquid volume of 100%, thereby obtaining the superionic conductor electrolytes of embodiments 3 to 8. Wherein, the anion part X of the ionic liquid [A]X of embodiments 3 to 7 is 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, and the anion part X of embodiment 8 is 5-hydroxy-2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid.

[0117] The compositions and physicochemical properties of Examples 3 to 8 are summarized in Table 3.

[0118] The experimental results show that the room temperature ionic conductivity of the superionic conductor electrolytes provided in Examples 3 to 8 is between 81 and 105 mS / cm, which has typical superionic conductor characteristics.

[0119] Furthermore, a low-temperature ion conductivity test was performed on the superionic conductor electrolyte provided in Example 3. The results showed that the ion conductivity at a low temperature of -19.1°C was 82.5 mS / cm (not shown in Table 3).

[0120] Furthermore, the superionic conductor electrolyte provided in Example 3 was subjected to a thermodynamic stability test. The results showed that its glass transition temperature was a low temperature of -46.2°C and its thermal decomposition temperature was +272.4°C (see Figure 3 , Figure 4 ). It is suggested that the superionic conductor electrolyte provided in Example 3 of the present invention remains stable in the temperature range of -46°C to +270°C, has the characteristics of a wide temperature range ionic liquid electrolyte, and its operating temperature range is much higher than the ideal low-temperature electrolyte standard.

[0121] Table 3 Composition and physicochemical properties of Examples 3 to 8

[0122]

[0123] The molar ratios are rounded to integers.

[0124] Examples 9-16

[0125] Embodiments 9 to 16 of the present invention provide a method for preparing a hybrid superionic conductor electrolyte, comprising: adding choline chloride (CHC) and 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, raw materials for forming [A]X, to a small amount of water in sequence according to the composition molar ratio (mol) and mass concentration (wt%) in Table 4, stirring for 10-30 min at room temperature until completely dissolved, first in situ synthesizing a required amount of ionic liquid [A]X; then doping different electrolyte salts respectively until completely dissolved, and supplementing water to a total liquid volume of 100%, thereby obtaining the hybrid superionic conductor electrolytes of embodiments 9 to 16.

[0126] The compositions and physicochemical properties of Examples 9 to 16 are summarized in Table 4.

[0127] The experimental results show that metal ion doping can lead to an increase in ionic conductivity. Compared with the above-mentioned Example 3, the ionic conductivity of lithium bromide (LiBr), lithium carbonate (Li2CO3), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), and lithium hexafluorophosphate (LiPF6) increased by ~20%, and the ionic conductivity increased accordingly with the increase of lithium salt concentration; the ionic conductivity of sodium chloride (NaCl) increased by ~42%; the ionic conductivity of magnesium sulfate (MgSO4) increased by about ~10%; the ionic conductivity of metal oxide (CeO2) increased by ~10%.

[0128] Among them, lithium carbonate and lithium hexafluorophosphate have low solubility in the ionic liquid [chc]X composed of choline chloride and 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, and lithium salts precipitate in the solution, but do not affect the change of ionic conductivity.

[0129] Table 4 Composition and physicochemical properties of Examples 9 to 16

[0130]

[0131] The molar ratios are rounded to integers.

[0132] Examples 17-20

[0133] Embodiments 17 to 20 of the present invention provide a method for preparing a quasi-solid-state flexible superionic conductor electrolyte, comprising: adding choline chloride (CHC) and 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, the raw materials for forming [A]X, to a small amount of water in sequence according to the composition molar ratio (mol) and mass concentration (wt%) in Table 5, stirring for 10-30 minutes at room temperature until completely dissolved, first in situ synthesizing the required amount of ionic liquid [A]X; then adding additives (lithium salt and polymer) in sequence and stirring until completely dissolved, supplementing water to a total liquid volume of 100%, thereby obtaining the quasi-solid-state flexible superionic conductor electrolyte of Embodiments 17 to 20.

[0134] The compositions and physicochemical properties of Examples 17 to 20 are summarized in Table 5.

[0135] The experimental results show that after adding polymer, a quasi-solid superionic conductor electrolyte is obtained, but the ionic conductivity can be reduced by 30%; the ionic conductivity further decreases with the increase of polymer amount and gel viscosity, but even when the PVA addition amount reaches 20wt% and the gel is almost non-flowing, its room temperature ionic conductivity is still as high as 13mS / cm. Among them, the adverse effect of polyvinyl pyrrolidone on ionic conductivity is weaker than that of polyvinyl alcohol; doping lithium salt in quasi-solid gel electrolyte can lead to an increase in ionic conductivity, and the ionic conductivity increases with the increase of lithium salt concentration.

[0136] Among them, Example 17 is a flowable gel formed by adding PVP (K-90, 10 wt%) to Example 3, and the ionic conductivity is reduced by 30% (101 mS / cm to 73 mS / cm) compared with Example 3;

[0137] Among them, Example 18 is a flowable gel obtained by adding lithium salt (LiBr, 10wt%) to Example 17, and the ionic conductivity is increased by 7% (73mS / cm to 78mS / cm) compared with Example 17;

[0138] In which, Example 19 is based on Example 18, but PVP is replaced with an equal amount of PVA (PVA1799, 10 wt%) to form a flowable gel, and the ionic conductivity is reduced by 18% (78 mS / cm to 64 mS / cm) compared with Example 18;

[0139] In which, Example 20 is based on Example 19, the amount of polymer PVP is further increased to 20wt% to obtain a viscous gel that hardly flows, and the ionic conductivity decreases by 80% (64mS / cm to 13mS / cm).

[0140] Table 5 Composition and physicochemical properties of Examples 17 to 20

[0141]

[0142] The molar ratios are rounded to integers.

[0143] Examples 21-22

[0144] Embodiments 21 to 22 of the present invention provide a method for preparing an alkaline battery superionic conductor electrolyte, comprising: adding choline chloride (CHC) and 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid, raw materials for forming [A]X, to a small amount of water in sequence according to the composition molar ratio (mol) and mass concentration (wt%) in Table 6, stirring for 10-30 minutes at room temperature until completely dissolved, firstly synthesizing a required amount of ionic liquid [A]X in situ; dissolving sodium hydroxide and potassium hydroxide in the remaining amount of water to prepare sodium hydroxide solution and potassium hydroxide solution, respectively, and slowly dripping them into the in situ synthesized ionic liquid [A] under continuous stirring, thereby obtaining the alkaline battery superionic conductor electrolyte of embodiments 21 to 22.

[0145] The compositions and physicochemical properties of Examples 21 and 22 are summarized in Table 6.

[0146] Examples 21 and 22 verify the compatibility of the superionic conductor electrolyte provided in the examples of the present application with sodium hydroxide and potassium hydroxide. The results show that sodium hydroxide and potassium hydroxide are compatible with the superionic conductor electrolyte at a concentration below 15wt% and greatly improve the ionic conductivity (>199mS / cm), and have superionic conductor characteristics. Superionic conductor electrolytes for alkaline batteries with a wide temperature range can optimize the electrochemical performance, safety and stability of existing alkaline batteries.

[0147] Table 6 Composition and physicochemical properties of Examples 21 to 18

[0148]

[0149] The molar ratios are rounded to integers.

[0150] Molecular simulation experiments

[0151] The ion pairs were screened through molecular simulation experiments, and the experimental results are summarized in Table 7.

[0152] Table 7 Molecular simulation experimental results

[0153]

[0154]

[0155] Molecular simulation experimental data show that under the conditions of 298.15K and 1.00Atm, in the reactions of 2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid and 5-hydroxy-2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid with choline, choline chloride, choline bromide, choline iodide, choline fluoride, choline chlorofluoride and β-methylcholine chloride, except for the Gibbs free energy change (ΔG≥0) of the reaction of 5-hydroxy-2-methyl-1,4,5,6-tetrahydropyrimidinecarboxylic acid with choline fluoride and choline chlorofluoride, which predicts that the reactions cannot proceed spontaneously, the Gibbs free energy changes (ΔG<0) of the other reactions predict that the reactions can proceed spontaneously, suggesting that stable ionic liquids can be formed.

[0156] In the ionic liquid that can be formed, strong hydrogen bonds are formed between molecules (bond energy BE ~ 23-98 Kcal / mol), so it has strong solubility and different polarities (dipole moment μ ~ 1.11-9.20 Debye). The experimental data is consistent with the results of the embodiment, and the electrolyte organic solvent can be completely replaced in the embodiment.

[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A superionic conductor electrolyte, characterized in that: The superionic conductor electrolyte comprises an ionic liquid [A]X, wherein [A] represents a cation part, X represents an anion part, [A] is derived from choline or a halide thereof, and X is derived from a pyrimidinecarboxylic acid derivative.

2. The superionic conductor electrolyte according to claim 1, characterized in that [A] is derived from any one of the compounds represented by the following structural formulas:

3. The superionic conductor electrolyte according to claim 1, characterized in that X is derived from the compound represented by the following structural formula: Wherein, R1 is selected from H or hydroxyl, and R2 is selected from C1-C4 alkyl; Preferably, X is derived from any one of the compounds represented by the following structural formulas:

4. The superionic conductor electrolyte according to any one of claims 1 to 3, characterized in that: The molar ratio of [A] to X is (1:1) to (14:1), preferably (2:1) to (10:1).

5. The superionic conductor electrolyte according to any one of claims 1 to 3, characterized in that: The superionic conductor electrolyte is a pure water-based superionic conductor electrolyte; the pure water-based superionic conductor electrolyte does not contain any organic solvent; Preferably, the superionic conductor electrolyte consists of water and ionic liquid [A]X; Preferably, the concentration of the ionic liquid [A]X in the superionic conductor electrolyte is 10-70 wt%.

6. A method for preparing the superionic conductor electrolyte according to claim 1, characterized in that: include: Mix and dissolve the raw material for forming the cation [A] and the raw material for forming the anion X; Preferably, the preparation is carried out under non-vacuum conditions; Preferably, the temperature of mixed dissolution is 30-50°C and the time is 10-30min; Preferably, water is used to dissolve the raw materials for forming the cation [A] and the raw materials for forming the anion X; Preferably, the process comprises: adding a raw material for forming a cation [A] and a raw material for forming an anion X into a small amount of water, stirring them conventionally at room temperature and pressure until they are completely dissolved, and synthesizing a required amount of ionic liquid [A]X in situ; and adding water until the total liquid volume is 100%.

7. A hybrid superionic conductor electrolyte, characterized in that: It comprises the superionic conductor electrolyte and an electrolyte additive as claimed in claim 1; the electrolyte additive is an electrolyte salt; Preferably, the electrolyte salt is selected from any one of lithium salt, sodium salt, aluminum salt, magnesium salt, zinc salt, copper salt and metal oxide; Preferably, the concentration of the electrolyte salt in the hybrid superionic conductor electrolyte is 5-30 wt %.

8. A quasi-solid flexible superionic conductor electrolyte, characterized in that: It comprises the superionic conductor electrolyte and electrolyte additive according to claim 1; the electrolyte additive is an electrolyte salt and a polymer; or the electrolyte additive is a polymer; Preferably, the electrolyte salt is selected from any one of lithium salt, sodium salt, aluminum salt, magnesium salt, zinc salt, copper salt and metal oxide; Preferably, the polymer is selected from any one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, polyvinylidene fluoride, polyacrylamide, agar, carrageenan, xanthan gum, sodium alginate and cellulose; Preferably, the concentration of the electrolyte salt in the quasi-solid flexible superionic conductor electrolyte is 5-30wt%; The concentration of the polymer in the quasi-solid flexible superionic conductor electrolyte is 5-20 wt %.

9. A superionic conductor electrolyte for an alkaline battery, characterized in that: It comprises the superionic conductor electrolyte and an electrolyte additive as claimed in claim 1; the electrolyte additive is selected from any one of sodium hydroxide and potassium hydroxide; Preferably, the concentration of the electrolyte additive in the alkaline battery superionic conductor electrolyte is 5-15 wt %.

10. An energy storage device, characterized in that: It comprises at least one of the superionic conductor electrolyte according to claim 1, the hybrid superionic conductor electrolyte according to claim 7, the quasi-solid-state flexible superionic conductor electrolyte according to claim 8, or the alkaline battery superionic conductor electrolyte according to claim 9, Preferably, the energy storage device comprises a battery and a supercapacitor; Preferably, the battery comprises any one of a wide temperature range lithium ion battery, a sodium ion battery, a magnesium ion battery, a zinc ion battery, a copper ion battery and a fuel cell.

Citation Information

Patent Citations

  • A solidified ionic liquid electrolyte, its preparation method and application

    CN106058312B

  • composite electrolyte amd a lithum battery including the same

    CN105390743A

  • Electrolyte composition and metal-ion battery employing the same

    CN111384445A

  • Pyrimidine ionic liquid as well as preparation method and application thereof

    CN118530183A

  • Electrolyte, electrolyte composition, and those application

    JP2010192226A

Cited By

  • Super-ionic conductor electrolyte and preparation method therefor, hybrid super-ionic conductor electrolyte, quasi-solid flexible super-ionic conductor electrolyte, super-ionic conductor electrolyte for alkaline batteries, and energy storage device

    WO2026152888A1